Cadmium Input to the Agricultural Soils with Phosphate Fertilizers in Turkey - YILDIZ, NESRIN; TURAN, METIN; BARIK, KENAN (Asian Journal of Chemistry, 2010)
Inorganic fertilizers are commonly used in conventional agriculture in Turkey as well as around the world. Inorganic fertilizers such as phosphorus fertilizer may cause an inadvertent addition of heavy metals. This study was conducted to determine the soluble and total cadmium content of phosphorus fertilizer's type used agricultural lands of Turkey. For this prupose, soluble and total cadmium content of four different phosphate fertilizers, which are normal super phosphate (NSP), di ammonium phosphate (DAP), triple super phosphate (TSP) and mono ammonium phosphate (MAP) were determined with graphite oven attached atomic absorption spectrophotometer. The results showed that NSP (850 μ kg-1) and DAP (2266 μ kg-1) fertilizers have maximum water soluble and total cadmium content, respectively. In respect of maximum permissible cadmium content (1 mg kg-1) of soils, it should be recognised that 2 mg kg-1 cadmium are supplemented to Turkish soils every year. With the estimation of 30.5 kg ha-1 phosphorus fertilizer use between 1972 and 2000 there for 2 g cadmium ha-1 was supplemented to Turkish soils within this period. Phosphorus fertilizers must be applied to the soil according to the crops' needs for phosphorus and available soil phosphorus status for sustainable agriculture. Future studies should be carried out to investigate cadmium and phosphorus downward movement and losses by leaching in soils.